2022
DOI: 10.3390/jcm11206080
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Assessment of Surgical Stress Response Using Nociception Monitor under General Anesthesia and Postoperative Complications: A Narrative Review

Abstract: We present a narrative review focusing on the new role of nociception monitor in intraoperative anesthetic management. Higher invasiveness of surgery elicits a higher degree of surgical stress responses including neuroendocrine-metabolic and inflammatory-immune responses, which are associated with the occurrence of major postoperative complications. Conversely, anesthetic management mitigates these responses. Furthermore, improper attenuation of nociceptive input and related autonomic effects may induce increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 87 publications
1
17
2
1
Order By: Relevance
“…The heterogeneity of the studies was moderate for pain intensity (I 2 = 48%) and low for opioid consumption (I 2 = 15%). We found no evidence of a significant difference between groups in duration of post-anaesthesia care unit stay nor in Our meta-analysis differs from previous reports in its focus on immediate postoperative pain, which is directly influenced by the quality of intra-operative analgesia [36].…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The heterogeneity of the studies was moderate for pain intensity (I 2 = 48%) and low for opioid consumption (I 2 = 15%). We found no evidence of a significant difference between groups in duration of post-anaesthesia care unit stay nor in Our meta-analysis differs from previous reports in its focus on immediate postoperative pain, which is directly influenced by the quality of intra-operative analgesia [36].…”
Section: Resultscontrasting
confidence: 99%
“…Our meta‐analysis differs from previous reports in its focus on immediate postoperative pain, which is directly influenced by the quality of intra‐operative analgesia [36]. However, it should be noted that the standard care varied between the included studies.…”
Section: Discussionmentioning
confidence: 94%
“…Changes produced in the hemato-immunological axis generate Th1 lymphocyte cell suppression, with a consecutive Th1/Th2 lymphocyte ratio reduction, favoring the appearance of infectious complications [ 13 ]. Sympatho-adrenomedullary axis (SAM) and the hypothalamic-pituitary adrenal-axis activation can be a trigger for the occurrence of cardiac, neurological, renal, hepatic, and coagulant dysfunction, thus increasing patients’ mortality and morbidity 30 days after surgery [ 14 ]. Long-term survival is also affected, and perioperative period changes create an environment favoring metastases’ occurrence [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The significant decrease in mean NR in patients with TEB represents lower levels of nociception during surgery than that in patients without TEB. [5] On the other hand, the increase in the LMR indicates an increase in lymphocyte counts or a decrease in monocyte, correlating with anti-inflammation, which suppresses morbidity or mortality. [14][15][16] Previous studies have revealed that increases in sympathetic activity, accompanied by excessive nociception, contribute to hematopoiesis in the bone marrow, including neutrophils and monocytes, [17,18] This excessive acute inflammation has been shown to cause postoperative complications.…”
Section: Discussionmentioning
confidence: 99%